MACLP: multi agent constraint logic programming - Vlahavas, Ioannis (Information sciences, 2002)
Multi Agent Systems (MAS) have become the key technology for decomposing complex problems in order to solve them more efficiently, or for problems distributed in nature. However, many industrial applications besides their distributed nature, also involve a large number of parameters and constraints among them, i.e. they are combinatorial. Solving such particularly hard problems efficiently requires programming tools that combine MAS technology with a programming schema that facilitates the modeling and solution of constraints. This paper presents MACLP (Multi Agent Constraint Logic Programming), a logic-programming platform for building, in a declarative way, multi agent systems with constraint-solving capabilities. MACLP extends CSPCONS, a logic programming system that permits distributed program execution through communicating sequential Prolog processes with constraints, by providing all the necessary facilities for communication between agents. These facilities abstract from the programmer all the low-level details of the communication and allow him to focus on the development of the agent itself.